Land use management and urban development in West Europe - Md. Yassin, Azlina (2004)
One of the most important resources is land. It's not only used for plantations but also for economic, politic, social and administrations purposes. Actually land is one of the symbols of "power". Therefore its must be managed properly for the optimum result and to avoid wasting. Cleverness in land matters management is a must. In order to manage the land resources, attention must be given to the benefit of all party and to the environments. From all the lectures and visit attended, the conclusion can be made that the land resource management in United Kingdom and Netherlands are good and systematic. Many things we learned from their experiences. Nevertheless the lectures given and the visit attended is only a small part in these countries. All these factors that are shown are only the best in their countries. However, the participants can do analysis on their own and compare to what we have done in our country. Apart of that Malaysia also have a good land resource and urban developments management and some of them we even do better than these two countries